Financial Report of Sangkuliman Kabupaten Kutai Kartanegara - Musdalifah; Rini Koen Inswandari (Poltanesa, 2025)
Sangkuliman Village, located in Kota Bangun District, Kutai Kartanegara Regency, is one of the leading tourism villages that capitalizes on its rich natural and cultural potential. Its main attractions such as Semayang Lake, Saguntur Lake, and the Mahakam River Dolphin (Pesut Mahakam) serve as key strengths for developing community-based tourism (CBT). Tourism activities are managed by the Tourism Awareness Group (Pokdarwis) BMT, which plays a central role in mobilizing community participation in managing local tourism resources. However, the financial management practices of Pokdarwis continue to face several critical challenges. Observations and interviews reveal that financial records are still maintained manually and rely solely on simple cash books, with no preparation of financial statements such as income statements or balance sheets. In addition, the use of personal funds by Pokdarwis administrators for operational needs without formal documentation poses administrative risks and undermines financial accountability. Findings from this study indicate that most Pokdarwis organizations have not yet implemented even a basic accounting system and have limited understanding of transparency and financial accountability principles. This condition is compounded by low human resource capacity, particularly regarding financial literacy and management skills. This research aims to describe the financial management system of Pokdarwis BMT in Sangkuliman Village, identify the challenges encountered, and develop strategic recommendations to establish a transparent, accountable, and sustainable financial governance system that ensures responsibility and long-term viability in managing community-based tourism.